Non-uniform contact characteristics of the friction disc during the initial period of a braking process - Qingrui, Meng; Zuzhi, Tian; Chenghao, Zhao (Journal of mechanical science and technology, 2018)
To reveal the contact characteristics of the hydraulic brake friction pair during the initial period of braking process and improve its working stability, by using ABAQUS software, we analyzed numerically the contact characteristics of the friction pair, including temperature, contact stress and heat flux variation laws of the contact surface. Theoretical analysis was verified by experiments. The results show that 1) the variations of the circumferential temperature distribution increase at first and then decrease; 2) the maximum value of the contact stress is near the inner edge of the friction disc, from t = 0.15 s the relatively larger contact stresses begin to intersperse on the entire contact surface; 3) heat flux distributions are similar to the temperature distributions; 4) the nonuniformity of the contact characteristics decreases with the increase of the friction disc thickness. It indicates that a friction disc of thickness 6 mm should be selected preferentially in the design of the hydraulic brake.